1975
DOI: 10.1029/ja080i031p04204
|View full text |Cite
|
Sign up to set email alerts
|

An empirical relationship between interplanetary conditions andDst

Abstract: An algorithm is presented for predicting the ground‐based Dst index solely from a knowledge of the velocity and density of the solar wind and the north‐south solar magnetospheric component of the interplanetary magnetic field. The three key elements of this model are an adjustment for solar wind dynamic pressure, an injection rate linearly proportional to the dawn‐to‐dusk component of the interplanetary electric field which is zero for electric fields below 0.5 mV m−1, and an exponential decay rate of the ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
1,353
3
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,279 publications
(1,401 citation statements)
references
References 23 publications
33
1,353
3
12
Order By: Relevance
“…However, storms occur generally when the interplanetary magnetic field (IMF) is strong and steady and not in intervals of fluctuating IMF (Russell et al, 1974;Russell et al, 2000). Using what was understood about the control of the reconnection by the IMF, Burton et al (1975) demonstrated that the ring current could be predicted from solar wind parameters with an extremely simple prescription. Energy is injected into the ring current at a rate proportional to the amount of convected southward IMF (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, storms occur generally when the interplanetary magnetic field (IMF) is strong and steady and not in intervals of fluctuating IMF (Russell et al, 1974;Russell et al, 2000). Using what was understood about the control of the reconnection by the IMF, Burton et al (1975) demonstrated that the ring current could be predicted from solar wind parameters with an extremely simple prescription. Energy is injected into the ring current at a rate proportional to the amount of convected southward IMF (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As well known the main source of magnetospheric disturbances including the magnetic storms is the southward component B z of interplanetary magnetic field (IMF) [Dungey, 1961;Fairfield and Cahill Jr, 1966;Rostoker and Falthammar, 1967;Russell et al, 1974;Burton et al, 1975;Akasofu, 1981]. In the steady types of the SW streams the IMF lies near the ecliptic plane, and these types are not geoeffective.…”
Section: Introductionmentioning
confidence: 99%
“…During the positive B z IMF the F -layer cannot rise up 350 km for the generation of scintillations. As shown by Burton et al (1975), Sizova and Zaitseva (1984), Pudovkin at al. (1985) the magnetospheric ring current intensity is strongly dependent on the variations of the B z IMF.…”
Section: Discussionmentioning
confidence: 84%